Kedudukan Anak Angkat Dalam Pewarisan Menurut Hukum Adat Batak Toba Di Desa Siogung-Ogung Kecamatan Pangururan Kabupaten Samosir - Valentinus Rolando Naibaho; Mei Sinta Uli Br. Sihombing (Widya Yuridika, 2021)
The traditional Batak Toba tribe adheres to the father's lineage system (patrilineal) so that the clan is arranged according to the father's lineage (patrilineal), in the Batak Toba community marriage is a living value to continue the offspring, therefore marriages that do not have children can do adoption. However, in its implementation there are still many conflicts and problems that occur in the position of adopted children in the Toba Batak customary tribe. Sources of data used in this paper are secondary collecting data that has been there before by collecting data contained in legislation relating to issues in this journal. According to the Batak Toba customary law adopted children have the same position as biological children, in Indonesia adoption must be carried out legally based on Indonesian Government Regulation No. 54 of 2007 concerning the implementation of adoption. The conclusion that we take is that the adopted child has the right to inheritance from his adoptive parents as long as the adopted child has followed all the processes in the Rajahon or inaugurated with a traditional ceremony.